Molecular and Physiological Effects of Magnesium–Polyphenolic Compound as Biostimulant in Drought Stress Mitigation in Tomato - Haytham Hamedeh; Shaula Antoni; Lorenzo Cocciaglia; Valentina Ciccolini (Plants, 2022)
Plant biostimulants are being recognized as innovative tools to improve sustainable agricultural practices to mitigate the drastic effects of climate change, which is leading to a severe reduction in agricultural yields. In this work, a new biostimulant (EnNuVi® ALPAN®) was evaluated for its effectiveness on tomato (Solanum lycopersicum Mill. cv. Rio Grande) plants subjected to water deficit conditions. The molecular effects were elucidated through transcriptomic RNA-seq and gene expression qPCR analysis and the physiological responses were evaluated through qualitative analysis of pigments and proline content, membrane stability, and lipid peroxidation. ALPAN® was shown to adjust the transcriptional response by upregulating genes involved in source to sink carbohydrate metabolism and translocation, stomatal closure, and cell homeostasis. ALPAN® was shown to mitigate the deteriorating effects of water deficit on the physiological status of the plants by stabilizing the levels of the photosynthetic pigments, regulating the accumulation of osmo-protectants, and preserving the cell wall lipid bilayer from oxidation. In conclusion, transcriptomic and physiological analysis provided insightful information on the biostimulant effects, indicating a positive role of ALPAN® foliar application in alleviating the negative costs of water deficit.